Sustainable High‐Performance Aqueous Batteries Enabled by Optimizing Electrolyte Composition - Raphael L. Streng; Samuel Reiser; Anatoliy Senyshyn; Sabrina Wager; Johannes Sterzinger; Peter Schneider; David Gryc; Mian Zahid Hussain; Aliaksandr S. Bandarenka (Advanced Science)
Abstract Lithium‐free aqueous batteries (LFABs) offer a sustainable alternative to lithium‐ion batteries for large‐scale energy storage, addressing issues like material scarcity and flammability. However, their economic viability is limited by low energy density and cycle life due to the narrow electrochemical stability window of water and active material dissolution. High‐concentration water‐in‐salt electrolytes typically used to tackle these issues are expensive and potentially hazardous. This work presents a novel, cost‐efficient electrolyte design using safe salts at lower concentrations. The influence of different cation species on the copper hexacyanoferrate cathode and polyimide anode is systematically explored, optimizing the electrolyte for improved cell voltage and cycling stability. The resulting battery, with a 1.8 mol kg⁻1 MgCl2 + 1.8 mol kg⁻1 KCl aqueous electrolyte, achieves a competitive energy density of 48 Wh kg⁻¹ and 95% efficiency. It also shows 70% capacity retention even at extremely high (dis‐)charge rates of 50 C and a maximum specific power of over 10000 W kg⁻¹, indicating its strong potential for supercapacitor applications. Utilizing exclusively inexpensive and safe salts, this work significantly advances the practical application of low‐cost LFABs for large‐scale energy storage.